Economic Rationalities of Loksado Indigenous in a Redenomination Perspective - Bulan Prabawani; Apriatni Endang Prihatini; Dinalestari Purbawati (JURNAL ILMU SOSIAL, 2019)
Dayak Meratus is one of the tribes in Indonesia consisting about 633 ethnic groups in total. The Dayak Meratus tribe represents the majority of the tribe in Indonesia which tends to be isolated, has a low formal education, and lacks of public facilities. This research was aimed at describing the economic rationalities of Tribe Dayak Meratus, a Loksado Indigenous in the Regency of Hulu Sungai Selatan, Borneo Island in term of redenomination perspective. This research is important since redenomination has potential to create hyperinflation if it was not implemented properly, especially related to the inland community in Indonesia which is more than 13,000 islands. The data collecting applied focus group discussion which involved the chair and member of the Tribe, also survey as the data triangulation of method. This research applied explanation building and frequency distribution for the data analysis. The results show that the Loksado Indigenous has a  marginal economy and formal education,but the Tribe has high social capital for its gotong royong (mutual cooperation) spirit and has sufficiently good financial literacy that forms good economic rationalities. In the term of redenomination, the economic rationalities would be essential to maintain so that economic crashes would not be occured. Redenomination for indigenous people would be considered the same as the change in currency that has occurred several times in Indonesia, in wchich the socialization was through conventional media.